Pancreas Transplantation Prevents Morphologic and Ultrastructural Changes in Pulmonary Parenchyma of Alloxan-Induced Diabetic Rats - Spadella, César Tadeu [UNESP]; Suarez, O. A. X. [UNESP]; Lucchesi, A. N. [UNESP]; Cataneo, Antonio José Maria [UNESP] (Elsevier B.V., 2010)
Purpose. The aim of this study was to evaluate whether pancreas transplantation (PT) is a suitable method for controlling histopathologic changes in lungs of alloxan-induced diabetic rats.Methods. Sixty inbred male Lewis rats were randomly assigned to 3 experimental groups: NC, 20 nondiabetic control rats; DC, 20 untreated diabetic control rats; and PT, 20 diabetic rats that received syngeneic PT from normal donor Lewis rats. Each group was further divided into 2 subgroups of 10 rats each, which were killed after 4 and 12 weeks of follow-up. Clinical and laboratory parameters, fresh and fixed lung weights, and fixed lung volumes were recorded for all rats. Total number of alveoli, alveolar perimeter, alveolar surface area, and alveolar epithelial (AE) and endothelial capillary (EC) basal laminae thickening were randomly measured in 5 rats from each subgroup by using an image analyzer. For light microscopy, 250 alveoli were analyzed in each subgroup. For electron microscopy, 50 electron micrographs were examined for each subgroup.Results. The DC rats showed elevated blood glucose and glycosylated hemoglobin levels, with insulin blood levels significantly lower than the NC rats (P < .001). Fresh and fixed lung weights and fixed volumes were significantly reduced in these rats, although their proportions to body weight were increased at 12 weeks (P < .01). The total number of alveoli in diabetic rats was higher than in control rats, whereas alveolar perimeter and surface area were significantly diminished (P < .01). AE and EC basal laminae were significantly thicker in DC than in NC (P < .01). Successful PT corrected all clinical and metabolic changes in diabetic rats, with sustained normoglycemia throughout the study. Morphologic and morphometric changes observed in diabetic lungs were completely prevented in PT rats from 4 weeks after transplant.Conclusion. We conclude that PT can control morphologic and ultrastructural changes in pulmonary parenchyma, suggesting a promising perspective for preventing other chronic diabetic lesions.